Makna Kemerdekaan Kristen Berdasarkan Galatia 5:1-4 - Faogosokhi Ndruru (SOTIRIA (Jurnal Theologia dan Pendidikan Agama Kristen), 2023)
This study aims to understand the meaning of Christian freedom based on Galatians 5:1-4. This study uses the exegesis method to find out the meaning of freedom in the text of Galatians 5: 1-4. from the exegesis it is obtained that People who have been freed by Christ from the Torah Law should not be slaves anymore to the inducements of others. That would mean wasting God's grace and salvation (5:1). But Christian freedom must not be misunderstood, as if it were possible to live without restraints (5:13). Because Christian freedom is freedom to practice love which concludes all the Torah Law which is a guideline for life is still valid (5:14-15). The gift of the Holy Spirit requires a way of living according to the Spirit, so that His fruit becomes visible (15:16-26). The principle of living according to the Spirit can be concluded in loving others in a real way as the implementation of the Law of Christ (6:1-3). God certainly cannot be mocked (6:4-8). He demands that believers practice love (6:9-10) . Here it is known that when the Son of God came to earth and was willing to suffer and even die on the cross in order to save mankind from the slavery of sin. Because the first man fell into sin and sin never broke or stopped, but continued to stick to the human person.